CLINICOPATHOLOGICAL ANALYSIS AND ASSOCIATION OF FINE NEEDLE ASPIRATION WITH THE DIFFERENT LYMPH NODE LESIONS IN RURAL SINDH. : J Peop Univ Med Health Sci. 2025:15(3), 10-17. http://doi.org/10.46536/jpumhs/2025/15.03.652 - Santosh Kumar Sidhwani1, Hadia Khursheed2, Erum Khaliq3, Hira Faisal4, Shaista Bakhat5, Hina Wasti6 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2025)
BACKGROUND: Using Fine needle aspiration cytology FNAC as a mode of investigation is helpful in knowing the common patterns of lymphadenopathies which assist in diagnosing the clinical pathology where there is a dilemma in reaching the final diagnosis. FNAC is effectively used for both superficial and deep soft tissue masses and the most commonly targeted sites are the lymph nodes, breast, thyroid, salivary glands, and skin thus eliminating the need for unnecessary surgical interventions such as open biopsies. OBJECTIVE: The aim of this study was to observe the most common diagnosis for FNAC in patients presenting with lymph node swellings in the outpatient department in patients of both genders and all age groups. METHODOLOGY: In this cross-sectional study, 297 patients were recruited from the rural areas of Sindh. All the samples were collected from “The Laboratory” from “February 2019” to “December 2019” after taking informed consent. The sampling method in this study was non-probability consecutive sampling. FNAC was performed in each patient after observing all aseptic measures, slides were prepared and evaluated by a panel of histopathologists. Quantitative data was represented by Mean and Standard Deviation while the qualitative data was represented by frequency and percentages. The chi-square test was used to determine the association of different clinical variables with the diagnosis. RESULTS: 297 patients, 113 (38%) were males and (184) 62% were females. The subjects’ ages ranged from 1 -75 years and were divided into 3 respective groups, (0-19 years, 20-39 years, and ≥40 years). The majority of the patients (128, 43.1%) fell in the 0-19 age group, followed by 124 (41.8%) patients in the 20-39 age group and only 45 individuals (15.2) were ≥40 years of age. The most common site of lymph node involvement was observed to be the cervical group with a total of 227 cases, of which 135 (45.5%) affected the right cervical group and 92 (31%) affected the left cervical group. This was followed by the right axillary group with 12 cases (4%) and the sub-mental group with 10 cases (3.4%). A sum of 192 cases was diagnosed with granulomatous inflammation by the histological findings, out of which 161 (54.2%) cases were Tuberculous/Chronic Specific Lymphadenitis and the remaining 31 (10.4%) were of tuberculous abscess. The next common lesion observed was Chronic non-specific lymphadenitis with 87 cases (29.3%). 12 cases (4%) were Suspicious of Malignancy. A significant association was observed between the cause of lymphadenopathy and the age of the patient (p value= 0.002), the site of the lymph node (0.002). CONCLUSION: In the current survey female of younger age groups were more frequently presented with right cervical lymphadenophies having chronic non- specific lymphadenitis. Age and site of the lymph node involved had an association with the diagnosis of FNAC.